Ginette Reno. L'histoire d'une superstar - Cellier, Gérard (Éditions Québécor, 1984)

Au-delà du mur du son, l’univers consonant et dissonant d’Anne Lauber - Cloutier, Diane (La Scène musicale, 1984)

La musique de salon au Québec (1880-1915) - Geoffrion, Diane (Les Cahiers de l'ARMuQ, 1984)

Écrire un théâtre musical. Transit. Entretien avec Micheline Coulombe Saint-Marcoux et France Théoret - Jonassaint, Jean (Dérives, 1984)

Emma Albani: Victorian Diva - MacDonald, Cheryl (Dundurn Press, 1984)
Talented Emma Albani was a favourite of Queen Victoria, singing at Victoria's funeral as well as Edward VII's coronation, and for many other heads of state from Russia, Austria, France, Italy, Belgium, Denmark, United States and Canada. Sir Arthur Sullivan, Gounod, Von Flotow and Dvorak wrotemusic for her and she sang with Nellie Melba, Adelina Patti, Jean de Reszke, Francesco Tamagno among others. Emma, who married Ernest Gye, manager of Covent Garden, was celebrated as one of the leading operatic and oratorio sopranos of the century. Emma (Lajeunesse) Albani, one of Canada's first internationally known performers, began as a student singing in a Chambly, Quebec convent and an Albany, New York church. From her opera debut in April 1870 in Sicily to her farewell concert in October 1911 in London, England, she was loved for her voice as well as her kindness, which was rare in a prima donna. She was adored by fans world-wide as George Bernard Shaw recorded in 1889," ... people were standing two and three deep behind the chairs ..., consisting of prima donna worshippers who are bent on obtaining a bird's eye view of Madam Albani.

Renaissance. Un récit bouleversant de sa lutte contre l'alcoolisme - Martel, Renée; Nantel, Linda (Presses libres, 1984)

Musique inuit au Québec arctique : contribution à une méthode d'analyse en anthropologie de la musique - Montpetit, Carmen; Veillet, Céline (Les Cahiers de l'ARMuQ, 1984)

Fabienne Thibeault... Cœur voyageur - Portelli, Rose-Marie (Éditions Plasma, 1984)

Diane Dufresne. Sa vie, ses amours, sa carrière, ses spectacles - Racine, Gaëtan (Éditions Québécor, 1984)
Femme aux milles visages, aussi excentrique que Boy George, Diane Dufresne est devenue en quelques années une véritable superstar qui compte des milliers d'admirateurs. Ce livre passionnant raconte sa vie: son enfance difficile, ses débuts de chanteuse, ses voyages, ses amours et son ascension fulgurante vers la gloire.